Rocking together: a report on a biological interaction between a non-native sea anemone and a sea squirt in southeastern Brazil - Ceriello, Hellen [UNESP]; Bazzo, Romulo A. O. [UNESP]; Martinez, Lucas D. [UNESP]; Chagas, Barbara M.t. [UNESP]; Lopes, Celine S.s.; Dias, Gustavo Muniz; Stampar, Sérgio N. [UNESP] (Instituto Oceanográfico da Universidade de São Paulo, 2025)
This study provides an in-depth examination of the ecological interaction between the non-native Diadumene lineata (Verrill, 1869) sea anemone, and the Polysyncraton amethysteum Van Name, 1902 colonial ascidian. We documented the nature of their interactions using systematic field observations carried out in their natural habitat along the rocky shores of Ubatuba, located on the northern coast of São Paulo State, Brazil. Our findings reveal that these two species engage in a complex relationship that may offer several adaptation strategies and ecological benefits, such as increased habitat stability and enhanced nutrient availability. We discuss how the presence of ascidians may provide shelter for the sea anemone. Furthermore, this study highlights broader implications of non-native species on rocky shore ecosystems. The introduction of non-native species can disrupt existing relationships between native organisms, potentially altering community structures and ecological balances.
Keywords: Actiniaria; Ascidiacea; Symbiosis; Southern Atlantic; Non-native species